Narrative Tensions in Strained Junior Elite Performers’ Experiences of Becoming Elite Performers - Haraldsen, Heidi M.; Abrahamsen, Frank E.; Solstad, Bård Erlend; Halvari, Hallgeir (Frontiers in Psychology, 2021)
Contextualized within narrative theory and the field of talent identification and development systems (TIDS), this interview study examined strained junior elite performers’ experiences of becoming elite performers while participating in prestigious national TIDS. The study explored how junior elite performers perceive and negotiate their personal narratives of becoming within a cultural master narrative of being. The focus is on how the quality of person-environment interaction, characterized by narrative alignment or tensions, relates to perceptions of identity, agency, physical, and mental health. We purposefully recruited eight participants (Mage = 17.31, SD = 0.90) from a previously published study, who reported experiencing sub-optimal psychological functioning compared with their peers, to explore narrative tensions in their storylines. The data were collected through semi-structured interviews and examined using narrative analysis. We identified “the performance narrative” as the dominating cultural narrative within the TIDS and three distinct personal narratives of negotiation with unique characteristics: obsessive and externally driven alignment—‘Striving to stay at the top of the game’; tensions—‘Just hanging in there’; and disruption from alignment—‘When the going gets tough’. The results indicated that tensions and lack of alignment between the dominating cultural narrative and the individual narrative seem to increase the risk of experiencing identity challenges, sub-optimal functioning, and aspects of ill-being. The study offers critical reflections on the dominating performance narrative within TIDS, and additionally suggests an alternative athlete-centered and more holistic approach that combines both personal and performance development.